Formoterol as reliever medication in asthma: a post-hoc analysis of the subgroup of the RELIEF study in East Asia. Issue 1 (December 2016) - Cheng, Qi; Huang, Shao-Guang; Chen, Yu; Lin, Jiang-Tao; Zhou, Xin; Chen, Bao-Yuan; Feng, Yu-Lin; Ling, Xia; Sears, Malcolm
Abstract Background As-needed formoterol can effectively relieve asthma symptoms. Since budesonide/formoterol is available as maintenance and reliever therapy in Asia, formoterol is now being used as-needed, but always with concomitant inhaled corticosteroids. The objective of this analysis was to assess the safety and efficacy of formoterol therapy in patients in East Asia (China, Indonesia, Korea, the Philippines and Singapore) with asthma. Methods Post-hoc analyses of data from the East Asian population of the RELIEF (REal LIfe EFfectiveness of Oxis® Turbuhaler® as-needed in asthmatic patients; study identification code: SD-037-0699) study were performed. Results This sub-group comprised 2834 randomised patients (formoteroln  = 1418; salbutamoln  = 1416) with mean age 35 years; 50.7 % were male. 2678 patients completed the study. There was no significant difference in the total number of adverse events (AEs) reported in the formoterol and salbutamol groups (21.3 % vs 20.9 % of patients;p  = 0.813), nor in the total number of serious AEs and/or discontinuations due to AEs (4.6 % vs 5.5 %, respectively;p  = 0.323). Compared with salbutamol, formoterol was associated with a significantly longer time to first exacerbation (hazard ratio 0.86;p  = 0.023) and a 14 % reduction in the risk of any exacerbation (p  < 0.05). Relative to salbutamol, mean adjusted reliever medication use throughout the study was significantly lower in the formoterol group (p  = 0.017) and the risk of increased asthma medication use was 20 % lower with formoterol (p  = 0.005). Conclusions Among patients with asthma in East Asia, as-needed formoterol and salbutamol had similar safety profiles but, compared with salbutamol, formoterol reduced the risk of exacerbations, increased the time to first exacerbation and reduced the need for reliever medication.